Ultrafast volumetric B1+ mapping for improved radiofrequency shimming in 3 tesla body MRI. Issue 4 (4th November 2013) - Sprinkart, Alois M.; Nehrke, Kay; Träber, Frank; Block, Wolfgang; Gieseke, Jürgen; Schmitz, Georg; Willinek, Winfried A.; Schild, Hans; Börnert, Peter
<x xml:space="preserve">Abstract</x> Purpose To evaluate the use of the recently proposed ultrafast B1+ mapping approach DREAM (Dual Refocusing Echo Acquisition Mode) for a refinement of patient adaptive radiofrequency (RF) shimming. Materials and Methods Volumetric DREAM B1+ calibration scans centered in the upper abdomen were acquired in 20 patients and three volunteers with written informed consent at a clinical dual source 3 Tesla (T) MR system. Based on these data, RF transmit settings were optimized by central‐slice based RF‐shimming (CS‐RF shim) and by a refined, multi‐slice adaptive approach (MS‐RF shim). Simulations were performed to compare flip angle accuracy and B1+ homogeneity (cv = stddev/mean) achieved by CS‐RF shim versus MS‐RF shim for transversal and coronal slices, and for volume shimming on the spine. Results By MS‐RF shim, mean deviation from nominal flip angle was reduced to less than 11% in all slices, all targets, and all subjects. Relative improvements in B1+ cv (MS‐RF shim versus CS‐RF) were up to 14%/39%/47% in transversal slices/coronal slices/ spine area. Conclusion Volumetric information about B1+ can be used to further improve the accuracy and homogeneity of the B1+ field yielding higher diagnostic confidence, and will also be of value for various quantitative methods which are sensitive to flip angle imperfections. J. Magn. Reson. Imaging 2014;40:857–863. © 2013 Wiley Periodicals, Inc.